Clinical Health Service Research on the Surgical Therapy of Acute Appendicitis. Issue 2 (August 2015) - Sahm, Maik; Pross, Matthias; Otto, Ronny; Koch, Andreas; Gastinger, Ingo; Lippert, Hans
<x xml:space="preserve">Abstract</x> Objective: The treatment of acute appendicitis has seen changes in diagnosis and therapy in Germany. The objective of this analysis was to assess changes in therapy and outcome after open appendectomy (OA) and laparoscopic appendectomy (LA) over the last 21 years. Background: The analysis was based on 3 prospective multicenter quality assurance studies conducted by the Institute for Quality Control in Operative Medicine of the University of Magdeburg. Methods: All inpatients with a diagnosis of appendicitis in these studies (1988/1989, 1996/1997, 2008/2009) were included. Multiple linear and logistic regression analyses were performed. Statistical significance was set at P < 0.05. Results: Data from 17, 732 treatments of patients diagnosed with appendicitis were collected. The average age of patients increased between the 3 studies from 25.7 to 34.6 years (P < 0.001). The preoperative selection of LA or OA was based on American Society of Anesthesiologists' classification (P < 0.001). Between 1996/1997 and 2008/2009, the share of LA climbed from 33.1% to 85.8% (P < 0.001). In the study from 2008 to 2009, LA showed a significant advantage over the conventional technique in wound healing disturbances (P < 0.001) and the clinical duration of stay (P < 0.001). At no stage of appendix inflammation did LA significantly increase intra-abdominal abscesses. The use of a stapler is currently the most common method of appendiceal stump closure (83.6%). Conclusions: Changes in patient data reflected demographic changes. Preoperative selection leads to 2 clearly defined groups. LA is the most dominant method of current operative therapy. The negative selection in OA group has influenced the worse outcome of that group.